University Students’ Perception on the Influence of the “Ideal” Media Body Image on their Choice of Clothing in Kenya - Nguchara , Nancy; Serem , Dorcas J.; Were , Gertrude M. (African Journal of Education,Science and Technology (AJEST), 2018)
c